A review and recent advances in solar-to-hydrogen energy conversion based on photocatalytic water splitting over doped-TiO2 nanoparticles - Ismael, Mohammed (Solar energy, 2020)
Photocatalytic hydrogen production under solar light irradiation is an attractive and appealing technology to produce green and renewable hydrogen fuel to reduce CO2 emission and air pollution. Due to its special physicochemical properties, TiO2 photocatalysts have been commonly used as a promising photocatalyst for hydrogen production. However, its wide bandgap energy, which can be only activated under UV-light and fast charge carriers recombination restricts their photocatalytic applications. Nevertheless, several approaches have been proposed to reduce its bandgap energy for visible light activity. Among them, the doping TiO2 with a dopant can be regarded as an effective method not only to cause a shift of the light absorption toward the visible region but also to diminish the charge recombination. This review concentrated on the influence of different types of dopants on the enhancement of the photocatalytic activity of TiO2. Furthermore, the methods of synthesis and the characterization techniques used for doped-TiO2 were carefully checked. Importantly, this review examined that the photocatalytic hydrogen production activity of the doped-TiO2 depends heavily on the type and concentration of the dopants. Furthermore, a metal-like Cu, noble metals like Au and Pt are the most widely studied dopants for TiO2 due to their superior work function. In addition, nitrogen was also widely used as a nonmetal owing to its ability to reduce the bandgap energy of TiO2. The findings also showed that the sol-gel method is still widely used in the preparation of doped-TiO2 photocatalysts due to the high crystallinity and surface area of the obtained nanoparticles.